Season does not have a deleterious effect on proportions of stallion seminal plasma proteins - Anders JOHANNISSON; Essraa M. AL-ESSAWE; Anas Kh. AL-SAFFAR; Saeid KARKEHABADI; Isabel LIMA-VERDE; Manuela WULF; Christine AURICH; Jane M. MORRELL (The Society for Reproduction and Development, 2020)
The mechanism by which the content of the major groups of seminal plasma proteins in stallion semen changes between the breeding and non-breeding seasons remains unknown. Here, we investigated the proportions of non-heparin-binding, phosphorylcholine-binding, and heparin-binding proteins in seminal plasma with the aim of relating them to sperm quality and testosterone levels in good and bad freezer stallions. Only minor variations in the major protein groups were found between the breeding and non-breeding seasons. In the non-breeding season, a higher content of a subset of non-heparin binding proteins as well as of heparin-binding proteins was found. Analysis of semen characteristics revealed a somewhat contrasting picture. While only minor variations in sperm kinematics and sperm morphology were found between seasons, the flow-cytometric measurements of mitochondrial membrane potential and also, to some extent, reactive oxygen species production indicated lower sperm quality in the breeding season. Chromatin integrity and testosterone levels were unchanged between seasons. The results suggest that stallion ejaculates could be used year-round for freezing, since only minor differences in protein composition exist between the breeding and non-breeding seasons, as well as between good and bad freezers. In addition, sperm quality is not impaired during the non-breeding season.